UK Climate Projections (UKCP18): Weather Patterns ... - Pope, James (Zenodo, 2024)
Provided here are the data files for the weather patterns generated for the 2018 UK Climate Projections (UKCP or UKCP18) Global ensemble (sometimes referred to as the land-gcm). The weather patterns are the same weather patterns as used in Neal et al. (2016) and used the same code to generate the weather patterns for the ensemble members. A historical equivalent of this dataset based on ERA5 can be found in Neal, (2022). The UKCP Global model dataset features two ensembles:The PPE-15 : A 15 member perturbed parameter ensemble of the HadGEM3.05 modelThe CMIP5-13: A sub-selection of 13 members from the CMIP5 ensemble. The PPE-15 data is available using the RCP 2.6 and RCP 8.5 scenarios and the CMIP5-13 is available only using the RCP 8.5 scenario. When using these weather patterns please cite: Pope et al., 2022, Investigation of future climate change over the British Isles using weather patterns. Climate Dynamics. ... : File descriptions: ukcp_weather_patterns_rcp85_ppe15.xlsx - The weather patterns for the UKCP Global PPE-15 ensemble membersfor the period 01/01/1900 to 30/11/2099 for the RCP8.5 scenario. ukcp_weather_patterns_rcp26_ppe15.xlsx - The weather patterns for the UKCP Global PPE-15 ensemble members for the period 01/01/1900 to 30/11/2099 for the RCP2.6 scenario. ukcp_weather_patterns_rcp85_cmip5-13_gregorian_calendar.xlsx - The weather patterns for the UKCP Global CMIP5-13 ensemble members using the Gregorian calendar for the period 01/01/1900 to 30/11/2099 for the RCP8.5 scenario. ukcp_weather_patterns_rcp85_cmip5-13_365_day_calendar.xlsx - The weather patterns for the UKCP Global CMIP5-13 ensemble members using a 365-day calendar for the period 01/01/1900 to 30/11/2099 for the RCP8.5 scenario. ukcp_weather_patterns_rcp85_cmip5-13_360_day_calendar.xlsx - The weather patterns for the UKCP Global CMIP5-13 ensemble member using a 360-day calendar for the period 01/01/1900 to 30/11/2099 for the RCP8.5 scenario. ...